Exploring Strategy, Text & Cases - Whittington, Richard; Regnér, Patrick; Angwin, Duncan; Johnson, Gerry; Scholes, Kevan (Pearson International Content, 2023)
Develop your strategic thinking, tackle real-world challenges and develop the skills to think and behave like a manager. With over a million copies sold worldwide, Exploring Strategy by Whittington, Angwin, Regnér, Johnson, and Scholes is the essential introduction to strategy for managers of today and tomorrow, tackling the hottest and most up-to-date issues regarding the operation of organisations. The latest 13th edition is renewed and revised according to the latest developments in the field, continuing the exploration surrounding the big questions about organisations: How does an organisation prosper today How do organisations grow How do they innovate and change? From entrepreneurial start-ups to multinationals and charities to government agencies, this industry-leading text includes extensive case studies and features to help you get a deeper understanding of the concepts and topics from theory to practice. This text and cases edition includes a wealth of additional case studies to help you get an even deeper insight into the manager-way of thinking. New to this edition: Think strategically and carry out case analyses and strategy assignments with the new chapter, 'Working with Strategy' Gain better insight into the three highlighted core themes: sustainability, non-profits, and digital strategy Learn from case studies of well-known global organisations, including Alibaba, Airbnb, Amazon, Alphabet, IKEA, and Uber. This Text and Cases version also covers a range of events and organisations such as Siemens, Mars, Formula 1, Glastonbury, and the Indian Premier League.